Members, Joiners, Free-riders, Supporters - Erik Ansink; Cees Withagen (Tinbergen Institute, 2015)
We augment the standard cartel formation game from non-cooperative coalition theory, often applied in the context of international environmental agreements on climate change, with the possibility that singletons support coalition formation without becoming coalition members themselves. Rather, their support takes the form of a monetary transfer to the coalition, which increases the members' payoffs, and thereby provides an incentive for other singletons to join the coalition. We show that, under mild conditions on the costs and benefits of contributing to the public good (i.e. abatement of CO2 emissions), supporters exist in equilibrium. The existence of supporters increases the size of stable coalitions, increases abatement of CO2 emissions, and increases payoffs to each of four types of agents: members, joiners, free-riders, and supporters. Importantly, this result does not require commitment.
Keywords: C72; D02; 330; Coalition formation; Public goods; Support; Transfers; International Environmental Agreements